Transforming the rural : global processes and local futures - Bjørkhaug, Hilde; Miele, Mara; Higgins, Vaughan, 1974-; Truninger, Mónica (Research in rural sociology and development, 2017)
This book analyses the key global processes transforming rural spaces in the early 21st century - financialization; standardization; consumption, and commodification. Through detailed case studies, the book examines why these processes are important, how they work in practice, and the challenges they raise as well as opportunities created.